Tooth color alteration after debonding in orthodontic patients with adhesive removal using composite bur or tungsten carbide bur: a single center, randomized controlled clinical trial - Sadrhaghighi, Amir Hooman; Mohammadi, Amir; Abdollahzadeh Baghaei, Tannaz; Alipour, Hamed (Brazilian Dental Science, 2020)
Introduction: The objective of this study was to determine whether recently developed fiber reinforced composite burs provided better results by comparing tooth discoloration after debonding of orthodontic brackets. Methods: A split-mouth, randomized controlled trial was carried out in one orthodontic office; including 23 patients with intact, vital and caries-free four upper incisors aged 12 to 30 years who completed their fixed orthodontic treatment. For each patient, upper central and lateral incisors on each side of the mouth were randomly selected to remove the adhesive with either a tungsten carbide bur (TC) (n = 46) or a fiber-reinforced composite bur (FC) (n=46). Color evaluation of each tooth was conducted at two time points: immediately after finishing and polishing procedure and two months afterwards. The primary outcome would be the amount of color change in each group during the post treatment phase. The participants, the person assessing the color change and the statistician were blinded to TC group assignment. Color changes in each group were analyzed with the Paired T-test. The color change corresponding to the resin removal method was also statistically analyzed with the Independent T-test at ?=0.05 as the level of significance. Results: 86 teeth, 43 in each group, were analyzed. The ?E value was 3.713±1.161, for teeth finished TC and 2.114±0.514 for teeth finished with FC (p<0.01). Conclusion: adhesive removal with FC bur results in a more color-resistant tooth surface in comparison with tungsten carbide bur.